Evaluasi Manajemen Risiko Teknologi Informasi Menggunakan COBIT 5 IT Risk (Studi Kasus : PT. Petrokimia Gresik) - Nurfitri Zukhrufatul Firdaus; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
SAP (System Application and Product in Data Processing) is a type of ERP Software that used by PT. Petrokimia Gresik to support business process automation and support decision-making process to be more effective and efficient. To anticipate the potential problems that might obstruct business processes at the company, so PT. Petrokimia Gresik managed to use risk management based on the standards of ISO 31000:2009. An evaluation on the implementation of IT risk management was done to measure its capability level accomplishment. COBIT 5 Framework, especially in process domain APO12 (Risk Management) dan EDM03 (Ensure Risk Optimation), was used as the basis of the evaluation. To collect accurate data, the data were obtained by filling evaluation worksheet, conducting a direct observation and an interview to the people in charge. The process of evaluating the implementation of IT risk management consists of several stages, including capability level analysis, gap analysis and risk assessment analysis to identify potential risks and assess the extent of the impacts of each risk. From the evaluation result, it turned out that capability level for process domain EDM03 was on level 2 and on level 3 for process domain APO12 and 16 mitigation strategy and 9 recommendation were made to support the improvement for the implementation of risk management information and technology at PT. Petrokimia Gresik.